Operationalising “loveability”: an interdisciplinary approach to enriching quality of life experiences in cities through creative cultural spaces - Rambhoros, Mizan; Neutra, Raymond Richard; Cerarols, Rosa; Pelowski, Matthew (Frontiers in Built Environment, 2025)
Loveability represents an emerging answer for enriching urban quality of life. The idea prioritises city dwellers’ emotional connections with psycho-spatial aspects of cities, beyond mere infrastructure, functionality, or services (“liveability”), which may not fully support positive wellbeing, especially in European cities. However, due to shifting, largely theoretical definitions and arguments for an unquantifiable nature, questions remain as to how people themselves think and feel about loveability within actual urban spaces. Here, for the first time we assessed how people quantify loveability, within two creative cultural or “third places:” MuseumsQuartier Haupthof in Vienna, Austria and Plaça de Joan Coromines in Barcelona, Spain. Based on a literature review, we identified potential psychological and spatial aspects associated with loveability and created a survey administered on-site to participants (N = 244) recruited from among foot traffic in our study settings. Participants rated spaces for liveability and loveability in their general experience of the places, and then defined how they had rated the “loveability” aspect via the importance of 55-items. Participants considered both places as loveable and contributing to positive wellbeing. Exploratory Factor Analysis and multiple regression models led to 5 factors for each population that highlighted groupings of significant psychological versus spatial dimensions. The distribution pattern showed commonalities of mostly psychological (e.g., delight/fascination, community, restorative wellness) but fewer spatial (usage/functionality) aspects across both settings. Our findings demonstrate that loveability plays a role in serving individuals’ delight and wellbeing, and insights of “accessibility,” “inclusivity,” and “order” may inform urban planning strategies and placemaking.